Employment Situation in Latin America and the Caribbean: Employment in microenterprises between 2003 and 2013. Improvements and challenges - NU. CEPAL (ECLAC, 2015)
The Employment Situation in Latin America and the Caribbean is a twice-yearly report prepared jointly by the Economic Development Division of the Economic Commission for Latin America and the Caribbean (ECLAC) and the Office for the Southern Cone of Latin America of the International Labour Organization (ILO).